Stress Perfusion CMR in Patients With Known and Suspected CAD: Prognostic Value and Optimal Ischemic Threshold for Revascularization - Vincenti, Gabriella; Masci, Pier Giorgio; Monney, Pierre; Rutz, Tobias; Hugelshofer, Sarah; Gaxherri, Mirdita; Muller, Olivier; Iglesias, Juan F; Eeckhout, Eric; Lorenzoni, Valentina; Pellaton, Cyril; Sierro, Christophe; et al. (JACC. Cardiovascular imaging, 2017)
This study sought to determine the ischemia threshold and additional prognostic factors that identify patients for safe deferral from revascularizations in a large cohort of all-comer patients with known or suspected coronary artery disease (CAD). Stress-perfusion cardiac magnetic resonance (CMR) is increasingly used in daily practice for ischemia detection. However, there is insufficient evidence about the ischemia burden that identifies patients who benefit from revascularization versus those with a good prognosis who receive drugs only. All patients with known or suspected CAD referred to stress-perfusion CMR for myocardial ischemia assessment were prospectively enrolled. The CMR examination included standard functional adenosine stress first-pass perfusion (gadobutrol 0.1 mmol/kg Gadovist, Bayer AG, Zurich, Switzerland) and late gadolinium enhancement (LGE) acquisitions. Presence of ischemia and ischemia burden (number of ischemic segments on a 16-segment model), and of scar and scar burden (number and transmurality of scar segments in a 17-segment model) were assessed. The primary endpoint was a composite of cardiac death, nonfatal myocardial infarction (MI), and late coronary revascularization (>90 days post-CMR); the secondary endpoint was a composite of cardiac death and nonfatal MI. During a follow-up of 2.5 ± 1.0 years, 86 and 32 of 1,024 patients (1,103 screened patients) experienced the primary and secondary endpoints, respectively. On Kaplan-Meier curves for the primary and secondary endpoints, patients without ischemia had excellent outcomes that did not differ from patients with <1.5 ischemic segments. In multivariate Cox regression analyses of the entire population and of the subgroups, ischemia burden (threshold: ≥1.5 ischemic segments) was consistently the strongest predictor of the primary and secondary endpoints with hazard ratios (HRs) of 7.42 to 8.72 (p < 0.001), whereas age (≥67 years), left ventricular ejection fraction (≤40%), and scar burden (LGE score ≥0.03) contributed significantly, but to a lesser extent, in all models with HRs of 2.01 to 3.48, 1.75 to 1.96, and 1.66 to 1.76, respectively. In a large all-comer patient cohort with known and suspected CAD, an ischemia burden of ≥1.5 ischemic segments on stress-perfusion CMR was the strongest predictor of the primary and secondary endpoints. Patients with zero or 1 ischemic segment can be safely deferred from revascularizations.